Dinasti Politik Dalam Pemilukada dan Otonomi Daerah: Kajian tentang Dinamika Pemilukada Tahun 2020 - Purwanto Putra; Roby Rakhmadi (Terekam Jejak Publisher, 2023)
The 2020 regional head election was the stage for the battle for political dynasties. This research discusses the various dynamics of political dynasties that have recently warmed up during the 2020 local elections, tracing the long history of dynastic politics in Indonesia, comparisons of dynastic politics in several countries, the impact and consequences of the phenomenon of political dynasties, and the relationship between political dynasties and regional elections and regional autonomy and concludes with a review of public attitudes and a settlement offer. The purpose of this study is to get a complete and actual description of the dynamics of various political dynasties. This study uses a qualitative-descriptive approach. Data collection in this study was carried out by emphasizing the exploration and collection of detailed information and the framework of generating new knowledge. Within the limitations due to the Covid-19 pandemic, this research tries to maximize the use of literature review with data collection methods by combining primary and secondary sources to obtain more holistic data and information. Researchers try to maximize the use of various sources from books or journals, documents from various relevant laws and regulations, as well as the latest and most trusted news sources. The results of this study indicate that dynastic politics has many impacts and consequences with a tendency to have negative impacts and threaten democracy. There is a direct connection between political dynasties, regional autonomy and regional elections. The practice of political dynasty is also a part of power which is not perfectly distributed. If this condition continues, it will also open up opportunities for the emergence of various abuses and has the potential to foster the growth of corrupt and collusive practices at the local level.